2006
DOI: 10.1111/j.1468-3083.2006.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy as an adjunct to systemic antimonials for cutaneous leishmaniasis in children

Abstract: 765 References1 Kragballe K, Beck HI, Sogaard H. Improvement of psoriasis by a topical vitamin D3 analogue (MC903) in a double-blind study. Br J Dermatol 1988; 119: 223 -230. 2 Dubertret L, Wallach D, Souteyrand P et al. Efficacy and safety of calcipotriol (MC903) ointment in psoriasis vulgaris. A randomised, double-blind, right/ left comparative, vehicle-controlled study. J Am Acad Dermatol 1992; 27: 983-988. 3 Ashcroft M, Li Wan Po A, Williams HC, Griffiths CEM. Systematic review of comparative efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Good cosmetic results after cryotherapy were described by previous investigators. 20,22,23,29 The accelerated healing process achieved through cryotherapy-as our efficacy results indicate-may be responsible for the low scarring rate. However, the clinical status of the lesion before treatment seems also to affect the extent of scarring.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Good cosmetic results after cryotherapy were described by previous investigators. 20,22,23,29 The accelerated healing process achieved through cryotherapy-as our efficacy results indicate-may be responsible for the low scarring rate. However, the clinical status of the lesion before treatment seems also to affect the extent of scarring.…”
Section: Discussionmentioning
confidence: 78%
“…Previous investigators have also found that color change due to cryotherapy was a transient side effect that resolves within months. 11,20,25,29 Although it is difficult to find a well-standardized scale for the assessment of scar quality in cases of CL, in general terms, scarring after cryotherapy was negligible in the majority (93.6%) of lesions. When noticeable, the scarring was not exaggerated and not beyond that which may occur after self-healing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5 Moreover, principals and methods that are being used for treating leishmaniasis in children are quite similar to those applied in adults. [6][7][8] Pentavalent antimony (Sb v ) drugs have been considered to be the first-line treatment of CL for over 50 years, 3 and still have high efficacy in the treatment of Old World CL. The improvement rate in endemic regions has been reported to be 17% for CL with L .…”
Section: Discussionmentioning
confidence: 99%
“…150 In a Greek report, cryotherapy has been added to low dose systemic antimonials to reduce the risk of adverse events secondary to antimonial therapy. 151 More recently, randomized controlled trials have been published that evaluate the efficacy of intralesional meglumine antimoniate, cryotherapy with a cotton applicator, and the combination of these modalities. In a 2004 randomized clinical trial performed in Iran, Asilian et al 70 reported that 120 of 132 lesions (90.9%) treated with combination cryotherapy and intralesional meglumine antimoniate were cured after one to three treatment sessions, whereas 120 of 210 lesions (57.15%) cleared with one to three sessions of cryotherapy alone, and 84 of 151 lesions (55.63%) cleared with one to three sessions of intralesional meglumine antimoniate alone.…”
Section: Cryotherapymentioning
confidence: 99%